The Attack Level of Cremastopsyche pendula Joannis Bagworm on Produce Palm Oil and Imature in Rambong Sialang Estate PTPP. London Sumatera Indonesia - Ronaldo Hasudungan Pangaribuan; Marheni Sembiring; Lahmuddin Lubis (Universitas Sumatera Utara, 2017)
This study aims to determine the level attacks of Cremastopsyche pendula of the age of oil palm trees on plantations and immature and crop yield. This research was conducted in the area of oil palm plantation in PTPP. London Sumatra Indonesia Rambong Sialang Estate in the village of Sialang Rambong Rampah Sei Serdang Bedagai using systemic random sampling method (systematic random sampling). The study started from January to March 2016. The results showed that the pest occurs more frequently in young plants compared to older plants. The highest percentage of attacks was on the block sample TBM 13.09% and attack percentage was lowest for the sample blocks TM 3.3%.